The 'Moralism' in Immoralism: A Critique of Immoralism in Aesthetics. (18th December 2018) - Paris, Panos
Abstract: According to immoralists, some artworks are better aesthetically in virtue of their immorality. A. W. Eaton recently offered a novel defence of this view, seeking to overcome shortcomings in previous accounts, thereby occasioning a reconsideration of immoralism. Yet, as I argue in this paper, Eaton's attempt is unsuccessful, insofar as it consists partly of inadequately supported claims, and partly—and more interestingly, albeit paradoxically—of covert moralist assumptions that are, eo ipso, incompatible with immoralism. I then turn to a parallel debate in ethics concerning the possibility of admirable immorality, suggesting that a consideration of the state of that debate further supports my argument against immoralism. I close by suggesting some strategies by which immoralists may offer a rejoinder, although I note that their prospects are rather dim, not least because available defences of immoralism and similar positions all seem to share the same flawed pattern.